F4+ ETEC infection and oral immunization with F4 fimbriae elicits an IL-17-dominated immune response. (December 2015) - Luo, Yu; Nguyen, Ut; Fe Rodriguez, Pedro; Devriendt, Bert; Cox, Eric
Abstract EnterotoxigenicEscherichia coli (ETEC) are an important cause of post-weaning diarrhea (PWD) in piglets. Porcine-specific ETEC strains possess different fimbrial subtypes of which F4 fimbriae are the most frequently associated with ETEC-induced diarrhea in piglets. These F4 fimbriae are potent oral immunogens that induce protective F4-specific IgA antibody secreting cells at intestinal tissues. Recently, T-helper 17 (Th17) cells have been implicated in the protection of the host against extracellular pathogens. However, it remains unknown if Th17 effector responses are needed to clear ETEC infections. In the present study, we aimed to elucidate if ETEC elicits a Th17 response in piglets and if F4 fimbriae trigger a similar response. F4+ ETEC infection upregulated IL-17A, IL-17F, IL-21 and IL-23p19, but not IL-12 and IFN-γ mRNA expression in the systemic and mucosal immune system. Similarly, oral immunization with F4 fimbriae triggered a Th17 signature evidenced by an upregulated mRNA expression of IL-17F, RORγt, IL-23p19 and IL-21 in the peripheral blood mononuclear cells (PBMCs). Intriguingly, IL-17A mRNA levels were unaltered. To further evaluate this difference between systemic and mucosal immune responses, we assayed the cytokine mRNA profile of F4 fimbriae stimulated PBMCs. F4 fimbriae induced IL-17A, IL-17F, IL-22 and IL-23p19, but downregulated IL-17B mRNA expression. Altogether, these data indicate a Th17 dominated response upon oral immunization with F4 fimbriae and F4+ ETEC infection. Our work also highlights that IL-17B and IL-17F participate in the immune response to protect the host against F4+ ETEC infection and could aid in the design of future ETEC vaccines.